2016
DOI: 10.1080/09603123.2016.1246654
|View full text |Cite
|
Sign up to set email alerts
|

Possible influence of the environmental pollutant bisphenol A on the cardiometabolic risk factors

Abstract: Bisphenol A (BPA) is a ubiquitous environmental pollutant which is often associated with various health issues. In this study 103 healthy female volunteers in reproductive age from Serbian north province Vojvodina were enrolled and examined for the BPA exposure in the urine samples after 12 h of fasting. BPA was found in 35.92 % (37/103) of subjects. Statistically significant increment in waist circumference (p = 0.045) and waist-to-height ratio (p = 0.037) was observed among the BPA positive women in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
0
17
1
Order By: Relevance
“…Surprisingly, we did not find a significant association between BPA and MetS, in contrast to findings from cross-sectional studies conducted among Lebanese (13) and Korean women (14). However, our results are similar to those among a sample of Serbian women of reproductive age (43). Differences between studies may be due to various reasons, such as varying study designs (most prior studies were crosssectional).…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
“…Surprisingly, we did not find a significant association between BPA and MetS, in contrast to findings from cross-sectional studies conducted among Lebanese (13) and Korean women (14). However, our results are similar to those among a sample of Serbian women of reproductive age (43). Differences between studies may be due to various reasons, such as varying study designs (most prior studies were crosssectional).…”
Section: Sensitivity Analysiscontrasting
confidence: 99%
“…A total of 5059 articles were identified; 108 abstracts were selected for full assessment; and 73 studies met our inclusion criteria (figure 1). Thirty studies were conducted in the USA, 17 in Europe, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] 22 in Asia, 2 in Latin America, 86 87 1 in Africa 88 and 1 in Canada. 89 In 72 studies, the anthropometric measures of obesity were assessed by trained health professionals, and in one study, weight and height were self-reported.…”
Section: Resultsmentioning
confidence: 99%
“…Unhealthy dietary habits and a sedentary lifestyle are considered the big two causes of such an increment, but there is a growing body of evidence suggesting a possible relationship between exposure to EDC and cardiometabolic health [ 25 ]. It must be said that almost all epidemiologic evidence on this issue comes from large cross-sectional studies and some cohort studies including women of all ages, whereas the evidence of an association between the exposure to EDC during the reproductive age and the risk of developing obesity, diabetes and cardiometabolic abnormalities is limited to few, generally small, cross-sectional studies [ 70 , 71 , 72 , 73 ].…”
Section: Edcs and Reproductive Healthmentioning
confidence: 99%
“…A small cross-sectional study involving 103 women aged 19–50 found that urinary BPA was associated with BMI and, marginally, with waist circumference, after adjustment for energy intake and energy requirement [ 70 ]. Similarly, another cross-sectional study, involving 246 healthy premenopausal women with regular menstrual cycles, found that the urinary BPA was modestly associated with BMI, waist circumference and fat mass assessed by DXA, after age-adjustment [ 71 ].…”
Section: Edcs and Reproductive Healthmentioning
confidence: 99%